Chickpea seed endophyte Enterobacter sp. mediated yield and nutritional enrichment of chickpea for improving human and livestock health - Mukherjee, Arpan; Gaurav, Anand Kumar; Chouhan, Gowardhan Kumar; Singh, Saurabh; Sarkar, Ankita; Abeysinghe, Saman; Verma, Jay Prakash (Frontiers in Nutrition, 2024)
Chickpea (Cicer arietinum L.) use as a good source of proteins and energy in mostly all living souls (Humans and animals) diets. Moreover, chickpea straws can serve as an alternative option of forage for different ruminants. This research mainly focused to screen the effects of adding beneficial chickpea seed endophytes on increasing the nutritional properties in the different edible parts of chickpea plants. Two efficient chickpea seed endophytes (Enterobacter sp. strain BHUJPCS-2 and BHUJPCS-8) were selected and applied with the chickpea seeds before sowing on the experimental conducted on clay pots. Chickpea seeds treated with the both endophytes showed improved plant growth and biomass accumulation. Notably, improvement of the uptake of mineral nutrients were found in foliage, pericarp and seed of the chickpea plants. Additionally, nutritional properties like total phenolics (0.47, 0.25, 0.55 fold), total protein (0.04, 0.21, 0.18 fold), carbohydrate content (0.31, 0.32, 0.31 fold), and total flavonoid content (0.45, 027, 0.8 fold) were increased in different parts (foliage, pericarp and seed) of the chickpea plants compared to the control plants. The seed endophytes treated plants showed significant increase in minerals accumulation and improvement in nutrition in the different edible parts of chickpea plants. The results showed that the seed endophyte-mediated increased in dietary and nutrients value of the different parts (pericarp, foliage and seeds) of chickpea are consumed by human whereas the other parts (pericarp and foliage) are used as alternative options of forage and chaff in livestock diets may have direct effects in their nutritional conditions.